1998
DOI: 10.1038/bjc.1998.130
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble intercellular adhesion molecule-1 (ICAM-1, CD54) in patients with non-small-cell lung cancer: correlation with histological expression of ICAM-1 and tumour stage

Abstract: Summary The expression of the intercellular adhesion molecule-1 (ICAM-1, CD54) seems to have an influence on the metastatic behaviour of tumour cells via immunological mechanisms. Recently, a soluble form of ICAM-1 was identified in physiological fluids. We analysed the serum levels of sICAM-1 in patients with non-small-cell lung cancer (NSCLC) and healthy individuals using a sandwich ELISA technique. Sera from 51 patients with NSCLC were tested for sICAM-1 (46 male, five female; age 38-81 years, median 64 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 42 publications
(34 reference statements)
1
33
0
3
Order By: Relevance
“…This ability would be explained by the regulation of many signaling molecules including drug transporters, cell proliferation regulators, members of the NF-κB signal transducer and activator of transcription 3 (STAT3) signaling pathways [78]. CD44 and CD54 played an important role in tumor metastasis by the mutual adhesion and interaction between cancer cells and vascular endothelial cells [79]. Tea polyphenols, known as catechins, have efects on cancer prevention, inhibition and anti-metastasis.…”
Section: Efects On Angiogenesis and Metastasismentioning
confidence: 99%
“…This ability would be explained by the regulation of many signaling molecules including drug transporters, cell proliferation regulators, members of the NF-κB signal transducer and activator of transcription 3 (STAT3) signaling pathways [78]. CD44 and CD54 played an important role in tumor metastasis by the mutual adhesion and interaction between cancer cells and vascular endothelial cells [79]. Tea polyphenols, known as catechins, have efects on cancer prevention, inhibition and anti-metastasis.…”
Section: Efects On Angiogenesis and Metastasismentioning
confidence: 99%
“…Similar to their normal hematopoietic and epithelial counterparts, leukemic cells and carcinomas express ICAM-1, which may be predicted to facilitate targeting by cytotoxic cells. However, ICAM-1 is shed from the surface of tumor cells, and serum levels of soluble ICAM-1 have even been proposed to provide an indicator of tumor burden (Grothey et al, 1998;Harning et al, 1991;Pizzolo et al, 1993). More to the point, shedding of ICAM-1 has been observed to inhibit cell mediated cytotoxicity and provide primary tumor cells as well as tumor cell lines with a mechanism of defense against cytolytic T cells and NK cells (Altomonte et al, 1993;Becker and Brocker, 1995;Becker et al, 1991;Fonsatti et al, 1997;Sanchez-Rovira et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that ICAM-1 was a marker of HCC stem cells, and increased numbers of CD45 -ICAM + tumor cells in blood samples of HCC patients correlated with worse clinical outcomes (19). On the other hand, circulating sICAM-1 has been reported to be elevated in the serum of patients with various malignancies (20)(21)(22)(23)(24)(25)(26)(27)(28). With regard to HCC, Shimizu et al reported that sICAM-1 ≥1,000 ng/ml was associated with poor prognosis in HCC patients who had been treated by transcatheter arterial chemoembolization (20), and Zhu et al reported that sICAM-1 >684 ng/ml was an independent prognostic factor for OS and RFS in HCC patients who had undergone surgical treatment (21).…”
Section: Discussionmentioning
confidence: 99%